Internet of things and blockchain integration for security and privacy - Kumar, Sumita; Vidhate, Amarsinh (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
The internet of things (IoT) can be defined as a network of intelligent objects where physical objects are equipped with electronic and network components to enable connectivity. These smart objects are embedded with sensors that enable them to monitor, sense, and gather data pertaining to their surroundings, including the environment and human activities. The applications of IoT, both existing and forthcoming, show great promise in terms of enhancing convenience, efficiency, and automation in our daily lives. However, for the widespread adoption and effective implementation of the IoT, addressing concerns related to security, authentication, privacy, and recovery from potential attacks is crucial. To achieve end-to-end security in IoT environments, it is imperative to define standard framework to achieve end to end security for the IoT applications. The blockchain is distributed ledge offers advantages such as confidentiality, authenticity, and availability. In this paper, we propose a novel framework to provide security and privacy for heterogeneous IoT architecture with integration of blockchain. The framework has provided an assessment framework to deploy, govern physical deployment. The proposed framework has defined standard architecture to integrate blockchain with layered IoT architecture with customization in blockchain with lightweight cryptography and consensus mechanism to overcome integration challenges and to achieve authenticity, security, and privacy.